An Assessment of the Nutritional Status of under Five Children in Four Districts in the Central Region of Ghana - Eunice , Ayensu; Sarah, Darkwa (Asian Journal of Agriculture and Rural Development, 2013)
The study determined the nutritional status of under five children in Komenda Edina EguafoAbirem (KEEA) districts in Central region, Ghana. Weight and height measurements for 120 children selected from 4 clusters were taken and survey data collected by structured questionnaire from mothers of the selected children. Prevalence of underweight/severely underweight stunting/severely stunted and wasting/severely wasted was 13.3%, 34.2% and 10.8% respectively. Results also indicated that stunting, wasting and underweight were more prevalent in girls than in boys and in children aged >2 - 5 years than those <2 years. Wasting only occurred in a small percentage of the boys and girls, and children <2 years.Survey revealed that there is a significant association between nutritional status of children and mothers’ age, education, nutrition knowledge and feeding practices. Wald statistics and confidence intervals after adjusting for mother’s age, education, occupation, father’s occupation and feeding practices showed mothers nutrition knowledge, feeding practices and mothers’ education as predictors of children nutrition status.Curbing teenage pregnancy, encouraging girls to pursue education, developing and implementing a comprehensive nutrition education programme for mothers with emphasis on providing quality nutritious and adequate food to children is highly recommended.